2015
DOI: 10.1073/pnas.1422594112
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by a chaperone improves substrate selectivity during cotranslational protein targeting

Abstract: The ribosome exit site is a crowded environment where numerous factors contact nascent polypeptides to influence their folding, localization, and quality control. Timely and accurate selection of nascent polypeptides into the correct pathway is essential for proper protein biogenesis. To understand how this is accomplished, we probe the mechanism by which nascent polypeptides are accurately sorted between the major cotranslational chaperone trigger factor (TF) and the essential cotranslational targeting machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…1 C ); this affinity is ∼900-fold higher than that of SecA for empty ribosomes ( Huber et al, 2011 ), suggesting additional interactions of SecA with the RodZ nascent chain. As other ribosome-associated protein biogenesis factors such as SRP and trigger factor (TF) could compete for binding to the ribosome and RodZ nascent chain under physiological conditions ( Ariosa et al, 2015 ; Gamerdinger et al, 2015 ), we further tested whether the SecA–RNC RodZ interaction survives the presence of these factors. Equilibrium titrations in the presence of near-physiological concentrations of SRP (400 nM) or TF (2 µM) showed that the SecA–RNC RodZ interaction was weakened by these factors but remained strong, with K d values of ∼19 nM and ∼55 nM, respectively ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 C ); this affinity is ∼900-fold higher than that of SecA for empty ribosomes ( Huber et al, 2011 ), suggesting additional interactions of SecA with the RodZ nascent chain. As other ribosome-associated protein biogenesis factors such as SRP and trigger factor (TF) could compete for binding to the ribosome and RodZ nascent chain under physiological conditions ( Ariosa et al, 2015 ; Gamerdinger et al, 2015 ), we further tested whether the SecA–RNC RodZ interaction survives the presence of these factors. Equilibrium titrations in the presence of near-physiological concentrations of SRP (400 nM) or TF (2 µM) showed that the SecA–RNC RodZ interaction was weakened by these factors but remained strong, with K d values of ∼19 nM and ∼55 nM, respectively ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Through the interaction between SRP and the SRP receptor (SR; termed FtsY in bacteria), the nascent protein is delivered to the SecYEG (or Sec61p) protein translocation machinery on the bacterial inner membrane (or the eukaryotic endoplasmic reticulum; Zhang et al, 2010 ). SRP-dependent targeting is complete before ∼130 amino acids of the nascent polypeptide C-terminal to the signal sequence or TMD is translated ( Siegel and Walter, 1988 ; Ariosa et al, 2015 ), and releasing nascent proteins from the ribosome abolishes the targeting of SRP-dependent substrates ( Kuruma et al, 2005 ). In bacteria, SRP is generally thought to mediate the targeted delivery of the majority of inner membrane proteins and several periplasmic secretory proteins that contain highly hydrophobic signal sequences ( Luirink and Sinning, 2004 ; Schibich et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A ribosome-associated chaperone called trigger factor (TF) interacts with proteins emerging from the tunnel 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 . The signal recognition particle (SRP) also binds to some nascent proteins, recognizing specific sequence motifs (signal sequences) and directing SRP-associated proteins for translocation through the inner membrane 42 43 44 45 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the processes mediated by the SIMIBI family of GTPases and ATPases are often constitutive and must occur rapidly. For example, co-translational protein targeting must occur before the nascent polypeptide reaches a critical length, which imposes a time window of 3–6 seconds for SRP and SR to complete each targeting cycle[72, 73]. The ability of SRP•SR and Get3 to directly respond to effector molecules in their respective pathways without the need to recruit extrinsic regulatory factors may be especially beneficial for vectorial processes that must occur efficiently.…”
Section: Comparison Of Srp•sr With Get3: Common Regulatory Principles?mentioning
confidence: 99%